Extensive glaciation in Transbaikalia, Siberia, at the Last Glacial Maximum. (15th January 2016) - Margold, Martin; Jansen, John D.; Gurinov, Artem L.; Codilean, Alexandru T.; Fink, David; Preusser, Frank; Reznichenko, Natalya V.; Mifsud, Charles
Abstract: Successively smaller glacial extents have been proposed for continental Eurasia during the stadials of the last glacial period leading up to the Last Glacial Maximum (LGM). At the same time the large mountainous region east of Lake Baikal, Transbaikalia, has remained unexplored in terms of glacial chronology despite clear geomorphological evidence of substantial past glaciations. We have applied cosmogenic 10 Be exposure dating and optically stimulated luminescence to establish the first quantitative glacial chronology for this region. Based on eighteen exposure ages from five moraine complexes, we propose that large mountain ice fields existed in the Kodar and Udokan mountains during Oxygen Isotope Stage 2, commensurate with the global LGM. These ice fields fed valley glaciers (>100 km in length) reaching down to the Chara Depression between the Kodar and Udokan mountains and to the valley of the Vitim River northwest of the Kodar Mountains. Two of the investigated moraines date to the Late Glacial, but indications of incomplete exposure among some of the sampled boulders obscure the specific details of the post-LGM glacial history. In addition to the LGM ice fields in the highest mountains of Transbaikalia, we report geomorphological evidence of a much more extensive, ice-cap type glaciation at a time that is yet to be firmly resolved. Highlights: Eighteen 10 Be exposure ages on moraines in high mountains of Transbaikalia, Siberia. Large ice fields existed in the mountains of Transbaikalia at the global LGM. Lower mountain ranges of Transbaikalia were also heavily glaciated at the LGM. Evidence exists for an extensive ice cap, the timing of which is yet to be resolved.